The Microbial Habitability of Weathered Volcanic Glass Inferred from Continuous Sensing Techniques - Bagshaw, Elizabeth A.; Cockell, Charles S.; Magan, Naresh; Wadham, Jemma L.; Venugopalan, T.; Sun, Tong; Mowlem, Matt; Croxford, Anthony J. (Mary Ann Leibert, 2011)
Basaltic glasses (hyaloclastite) are a widespread habitat for life in volcanic environments, yet their interior physical conditions are poorly characterized. We investigated the characteristics of exposed weathered basaltic glass from a surface outcrop in Iceland, using microprobes capable of continuous sensing, to determine whether the physical conditions in the rock interior are hospitable to microbial life. The material provided thermal protection from freeze-thaw and rapid temperature fluctuations, similar to data reported for other rock types. Water activity experiments showed that at moisture contents less than 13% wet weight, the glass and its weathering product, palagonite, had a water activity below levels suitable for bacterial growth. In pore spaces, however, these higher moisture conditions might be maintained for many days after a precipitation event. Gas exchange between the rock interior and exterior was rapid (<10 min) when the rocks were dry, but when saturated with water, equilibration took many hours. During this period, we demonstrated the potential for low oxygen conditions within the rock caused by respiratory stimulation of the heterotrophic community within. These conditions might exist within subglacial environments during the formation of the rocks or in micro-environments in the interior of exposed rocks. The experiments showed that microbial communities at the site studied here could potentially be active for 39% of the year, if the depth of the community within the outcrop maintains a balance between access to liquid water and adequate protection from freezing. In the absence of precipitation, the interior of weathered basaltic glass is an extreme and life-limiting environment for microorganisms on Earth and other planets. Key Words: Basaltic glass-Palagonite-Oxygen sensing-Cryptoendoliths-Life in extreme environments.
Keywords: Basaltic glass; Palagonite; Oxygen sensing; Cryptoendoliths; Life in extreme environments